Incidence of lower limb amputation in diabetic patients in Osijek-Baranja County - Canecki-Varžić, Silvija (Array, 2020)
Amputation of the lower limb (LLA) is one of the most feared adverse outcomes among diabetic patients. Our aim was to determine the incidence of amputation in diabetic patients in Osijek-Baranja County and to examine the possible correlation between clinical characteristics of the patients and the time elapsed before the first amputation. This was a tertiary-care-based retrospective study and included 925 diabetic patients who underwent non-traumatic lower limb amputation in the University Hospital Osijek from January 1st 2008 to December 31st 2018. Data on associated cardiovascular risk factors and clinical characteristics of the patients were collected from diabetic registry of the Department of diabetes and endocrinology. A total of 278 patients had all data for further analysis. There were 1551 LLAs over a ten year period. The incidence was 6.14 per 1,000 adults with diabetes. LLA rates per 1,000 adults with diabetes decreased by 29% between 2010 and 2013 and then increased by 76% between 2014 and 2018. In ten year period incidence of amputation in diabetic patients varied from 4 to 7.8 per 1000 persons-year. We observed the same pattern in both minor and major LLA but rates of amputation above knee steadily increased 2.7 times between 2010 and 2018 (from 0.69 to 1.83 per 1000 patients-year). The mean age of patients with LLA was 67.2 years, 66% were male, mean BMI was 29.6±4.8 kg/m2 and the mean duration of diabetes was 14.7±8.2 years. There was no association between smoking, arterial hypertension and hyperlipemia, ACE inhibitor use, statin use, antiplatelet use, CVD, neuropathy and duration of diabetes before first amputation. Only sulphonylurea and insulin therapy significantly prolonged the time before the first amputation (p = 0.00001, for each). In conclusion, our study confirmed high rate of lower limb amputation in diabetic patients in Osijek-Baranja County.